2013
DOI: 10.1186/1479-5876-11-21
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cell-like cells derived from autologous bone mesenchymal stem cells for the treatment of patients with cerebral palsy

Abstract: BackgroundStem cell therapy is a promising treatment for cerebral palsy, which refers to a category of brain diseases that are associated with chronic motor disability in children. Autologous MSCs may be a better cell source and have been studied for the treatment of cerebral palsy because of their functions in tissue repair and the regulation of immunological processes.MethodsTo assess neural stem cell–like (NSC-like) cells derived from autologous marrow mesenchymal stem cells as a novel treatment for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 31 publications
2
81
0
Order By: Relevance
“…Gonzalez et al [13] showed that MSCs can express pluripotency-related genes, and even more interesting these MSCs were isolated from adult human testes, which could indicate that these cells and PO-MSCs originate from the same cells in the developmental stage of indifferent gonads. Moreover, there are more and more studies confirming the trans-differentiation potential of MSCs [49][50][51][52][53][54][55] which makes them still more interesting to be applied in regenerative medicine and cellular therapies in the future. In the case of cells cultured in this study, we would particularly suggest using them in the frame of restoring ovarian function in cases of its impairment or of premature ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
“…Gonzalez et al [13] showed that MSCs can express pluripotency-related genes, and even more interesting these MSCs were isolated from adult human testes, which could indicate that these cells and PO-MSCs originate from the same cells in the developmental stage of indifferent gonads. Moreover, there are more and more studies confirming the trans-differentiation potential of MSCs [49][50][51][52][53][54][55] which makes them still more interesting to be applied in regenerative medicine and cellular therapies in the future. In the case of cells cultured in this study, we would particularly suggest using them in the frame of restoring ovarian function in cases of its impairment or of premature ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, experts showed that neural stem cell derived from autologous bone MSC are safe and effective for treatment of motor deficits related to cerebral palsy [53]. As a result, one new area in treatment of CNS disease is the application of the NSC.…”
Section: Allogeneic Umbilical Cord Msc (Ucmsc)mentioning
confidence: 99%
“…Therefore, it seems that these kinds of stem cells are not the optimal candidates for stem cell-based therapy. Nevertheless, there are studies that have shown hMSC emerge phenotypes and can differentiate into NSC-like cells in vitro [53]. Neurotrophic cytokines, such as human epidermal growth factor (hEGF) and bovine fibroblast growth factor (bFGF) can induce mesenchymal stem cells to differentiate into NSC.…”
Section: Allogeneic Umbilical Cord Msc (Ucmsc)mentioning
confidence: 99%
“…In order to prepare NSC-like cells, bone marrow aspiration, isolation and cultivation of MSCs, induction of NSCs and cell preparation were performed as previously described (14,17). Briefly, 5 ml bone marrow was obtained by puncture in the posterior iliac crest of each patient according to the conventional bone marrow aspiration procedures.…”
Section: Preparation and Transplantation Of Autologous Nsc-like Cellsmentioning
confidence: 99%
“…Although the functional mechanisms of this therapy have yet to be determined, these previous studies demonstrated that stem cell administration improves functional recovery following TBI in experimental animals. In addition, transplantation of stem cells has been successfully used in a clinical trial for patients with amyotrophic lateral sclerosis, multiple sclerosis and cerebral palsy (12)(13)(14). Thus, stem cell transplantation may be an attractive approach to restore brain function after TBI in humans.…”
Section: Introductionmentioning
confidence: 99%